Where Urban Residents Shop for Produce - Allison Karpyn; Karyn Tappe; Amy Hillier; Carolyn Cannuscio; Julia Koprak; Karen Glanz (Journal of Agriculture, Food Systems, and Community Development, 2016)
There is limited research documenting the shopping behaviors of urban residents with regard to where they shop for fruits and vegetables. This study sought to: (1) describe characteristics of consumers who shop for produce at supermarkets, alternative fresh food outlets, and farmers' markets; and (2) identify correlates of farmers' market shopping among urban consumers. Participants were recruited from 30 randomly selected residential blocks in West and Southwest Philadelphia, Pennsylvania, to complete a cross-sectional survey. Of 622 residents contacted, 82.6 percent completed a usable survey. Participants were predominantly African American (75.2 percent), single (47 percent), and receiving public assistance (30.1 percent). About half of the respondents reported shopping at farmers' markets (48.2 percent), produce stores (47.9 percent), and/or fruit and vegetable trucks (48.0 percent percent) for produce. Having vouchers for farmers' markets was significantly associated with shopping at those markets, being younger, and not owning a car. Our analysis begins to bridge the gap in understanding how individual-level differences may influence shopping patterns. Findings suggest that financial incentives to shop at farmers' markets can be meaningful contributors to shopping at these venues and may work to support the narrowing of disparities in access to healthy, affordable food.